ETHNOMATHEMATICS OF SMALL BORDER ISLANDS: LUTUR BATU ON MOA ISLAND - Sugiarto, Sigit; Rupilele, Karolina; MA, Ratnah Kurniati; Lekitoo, John Nandito; Inuhan, Michael; Dahoklory, Andy Sunder Keer (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2024)
The people of Moa Island have a cultural heritage in the form of Lutur Batu. Lutur Batu is a construction of large stones arranged side by side to form a circular wall. Lutur Batu is used to close village boundaries and as a garden fence which aims to protect plants from wild animals. This research aims to determine ethnomathematics studies on Lutur Batu on Moa Island. The ethnomathematics study of Lutur Batu on Moa Island in this research is expected to provide a deeper understanding of the local wisdom of the people of Moa Island, as well as contribute to the recognition, maintenance, and preservation of cultural heritage with mathematical value in the region. Furthermore, an understanding of the geometric patterns and construction of Lutur Batu can be adopted in mathematics learning at school to increase students' interest in learning and understanding of mathematical concepts.This qualitative research focuses on an in-depth understanding of ways of thinking and using mathematics in the traditions and practices of making Lutur Batu in Moa Island. The results of the analysis on Lutur Batu and the manufacturing process showed that there are mathematical concepts such as circles, cylinders, comparisons, and statistics. Lutur Batu and the Mathematical concepts contained therein can be used in Mathematics learning at school to enrich learning materials, increase learning motivation and students' understanding of Mathematics concepts. Apart from that, it can increase students' insight and knowledge regarding the cultural heritage of Moa Island